Diagnostic accuracy between ultrasound and radiography in detecting greenstick fracture with various angulations on pediatric by using homemade distal radius phantom / Nurul Aisyah Mohammad Noor and Lyana Shahirah Mohamad Yamin - Mohammad Noor, Nurul Aisyah; Mohamad Yamin, Lyana Shahirah (2020)
The aim of this study is to compare the effectiveness of the ultrasound and radiography in detecting greenstick fracture with different angulations on pediatric by using homemade distal radius phantom. Ten homemade phantoms consist of chicken leg bones and gelatine had been prepared to represent the pediatric distal radius. There are two sets of phantoms where each contain two normal chicken leg bones and three chicken leg bones with different angulations of greenstick fracture start with 10°, 20° and 30°. Three emergency physicians were then evaluated all of the phantoms through ultrasound images and radiographic images to obtain diagnostic accuracy results. Based on the result, ultrasound has high specificity (100%) with low sensitivity (55.6%) while the radiography has low specificity (50.0%) and sensitivity (44.4%). From this study, the ultrasound is more effective in detecting greenstick fracture with different angulations on pediatric distal radius by using the phantoms as compared to radiography test.